PENGARUH BEBERAPA FAKTOR FUNDAMENTAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP HARGA SAHAM (studi pada perusahaan yang terdaftar dalam indeks LQ45 di BEI) - Efendi, Ahmad; Destalia, Mediya; Wulandari, Jeni; Pratama, Maulana Agung (JURNAL PERSPEKTIF BISNIS, 2013)
The financial report is a medium of communication used by the company. Provision of regular financial reports by publicly traded companies interpreted each publicly traded company that has gained the participation or attempt to maintain stability and increase the stock price that has been sold. The stock price is defined as the market price (market value), that is the price prevailing in the market at a given time. Appraisal (valuation) usually refers to the estimated intrinsic value of a company or its shares. In assessing a stock can be used two methods of analysis, namely technical analysis and fundamental analysis. Besides influenced by fundamental factors which are variable in fundamental analysis, stock prices are also often influenced by the growth of the company.This study took samples from 15 companies in a company incorporated in LQ 45 in Indonesian Stock Exchange is publishing the report of the years 2004 to 2008. Moreover also the data obtained from ICMD (Indonesian Capital Market Directory). This research is explanatory researce associative and analytical methods used are multiple regression analysis to explain the influence of independent variables and the dependent variable.Results from this study show simultaneous existence of a significant effect of ROE, EPS, PER, Interest Rates, Inflation, and Total Assets of Stock Price. Partially, ROE has a significant positive effect on stock price, EPS is a significant positive influence stock price, PER significant negative effect on Stock Prices, Interest Rates significant negative effect on Stock Prices, Inflation negatih no significant effect on stock price and changes in Total Assets have positive no significant effect on stock price